2019
DOI: 10.1002/jib.581
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of volatile compounds in Maotai flavour liquor during fermentation and distillation

Abstract: Volatile constituents in raw liquor and zaopei during fermentation and distillation were investigated by gas chromatography. Zaopei (steamed grains mixed with Daqu [FG1], stacking fermented grains [FG2], anaerobic fermented grains [FG3] and steamed grains [FG4]) presented changes in physicochemical properties. In all, 72 volatile compounds were identified in zaopei and raw liquor with similarity across 12 zaopei preparations. Principal component analysis and partial least squares discriminant analysis differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Succinic acid, a main product of the TCA cycle, is known as the “wine skeleton” (Zhang et al, 2017 ) and, when combined with lactic acid, provides the unique sourness and umami taste to the final product. Additionally, lactic acid is the central precursor of ethyl lactate, which is the key flavoring component in liquor (Cai et al, 2019 ; Liu and Miao, 2020 ). Meanwhile, fumaric acid improves the stability and freshness of wine and decreases the level of SO 2 (Morata et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinic acid, a main product of the TCA cycle, is known as the “wine skeleton” (Zhang et al, 2017 ) and, when combined with lactic acid, provides the unique sourness and umami taste to the final product. Additionally, lactic acid is the central precursor of ethyl lactate, which is the key flavoring component in liquor (Cai et al, 2019 ; Liu and Miao, 2020 ). Meanwhile, fumaric acid improves the stability and freshness of wine and decreases the level of SO 2 (Morata et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…These fatty acids are involved in the composition of liquor flavor in liquor and are also associated with various health-related functions. For instance, linoleic acid and stearic acid, which are present in myrtle liqueur (Correddu et al, 2019 ), Maotai flavor liquor (Cai et al, 2019 ), and cacao liquor (Osakabe et al, 1998 ), have been reported to exhibit antitumor, antiobesity, antidiabetic, and anti-inflammatory properties (Jaudszus et al, 2016 ). Moreover, arachidic acid, a C20 saturated fatty acid, was implicated in the incidence of atherosclerosis and coronary heart disease (Rivellese et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…The organic acids and alcohols could combine each other to form several esters, such as ethyl acetate . It was found that more ethyl acetate was produced during liquor fermentation, and became a key volatile compound of liquor during liquor brewing process (Cai et al, 2019). However, little research reported that ethyl acetate could increase to high level during vegetable fermentation.…”
Section: Fingerprint Analysis Of Volatile Compounds In Fmpmentioning
confidence: 99%
“…1,2-PG has been applied as a potential signature c for authenticity verification in alcoholic beverages such as wine and be Understanding the natural enantiomeric composition of 1,2-PG is importa authenticity assessing in wine, so as in Baijiu. 1,2-PG was detected in raw liquor flavour Baijiu [29] as well as the mechanized brewing of strong-flavor Baijiu [3 The distribution and concentration of the two isomers of 1,2-PG in Baijiu ar Therefore, the aim of this work was to isolate and determine (S)-1,2-PG and (R SSB, STB, LTB and the corresponding vintages to explore whether the distrib content of the two isomers of 1,2-PG are correlated with the aroma type and ag…”
Section: Introductionmentioning
confidence: 97%
“…Understanding the natural enantiomeric composition of 1,2-PG is important for the authenticity assessing in wine, so as in Baijiu. 1,2-PG was detected in raw liquor of Maotai flavour Baijiu [ 29 ] as well as the mechanized brewing of strong-flavor Baijiu [ 30 ].…”
Section: Introductionmentioning
confidence: 99%